ANALISIS RISIKO DAN MITIGASI PENGUSAHAAN PANAS BUMI: STUDI KASUS SURVEI PENDAHULUAN DAN PENGEBORAN EKSPLORASI PANAS BUMI UNTUK PEMBANGUNAN PLTP 20 MWe DI HALMAHERA UTARA, PROVINSI MALUKU UTARA - Aperta Ledy Alam; Herlinawati Herlinawati (JURNAL GEOMINERBA (JURNAL GEOLOGI, MINERAL DAN BATUBARA), 2021)
Geothermal business development into electricity energy resources is one of the efforts to develop renewable energy to replace energy resources from fossil. Developing geothermal green field in North Halmahera, North Maluku Province are activities that have risk in the implementation action. The SWOT method will raise some parameters that are risk factors in geothermal field development. Risk parameters are data source of geology subsurface, value of geothermal resources, economic condition (financing), social and culture condition, also environmental impact. Every risk needs to be mitigated in geothermal field development plan. Risk analysis in geothermal filed development uses the risk grading matrix method which is a qualitative analysis method that determine degree of risk based on impact and probability. All risks factor has high to moderate impact with high to moderate probability. Qualitatively, using mitigation, will reduce impact and probability of risks become moderate to low. This support to continue attempt geothermal field development at North Halmahera, North Maluku Province.